Strategies For Handling The Spread Of Covid-19 In Klungkung District - Mertasih, Ni Luh; Dewi, Nyoman Diah Utari; Widanti, Ni Putu Tirka (Spirit Publik: Jurnal Administrasi Publik, 2023)
The Village government's strategy in dealing with Covid-19 is based on the Circular Letter of the Klungkung Regent Number 411/176/BPBD concerning the Extension of Restrictions on Village/Kelurahan-Based Micro Community Activities and Optimizing the Covid-19 Handling Post at the Village/Kelurahan level to control the spread of Covid19 in Klungkung Regency . This research is a qualitative descriptive study. The theoretical basis used in this study is the Implementation Theory of Merilee S Grindle (1980) in Subarsono (2021:93) explaining that implementation is influenced by two major variables, namely the content of the policy and the implementation environment (context). The results of the analysis show that the implementation of handling the spread of Covid-19 in the Semarapura Kangin Village, Klungkung District, Klungkung Regency has not run optimally because there are still negative benefits and negative impacts on the implementation of the policy, the low level of community compliance with the policy. Obstacles in implementing the policy are lack of education, low community discipline, lack of socialization and budget constraints, these conditions can be overcome by increasing socialization and education so as to increase public awareness and discipline to comply with health protocols and budget refocusing in handling the spread of Covid19 . The strategy in handling the spread of Covid-19 is carried out with integrated cooperation between the Semarapura Kangin Village government, Klungkung District and the Covid-19 task force, BPBD, PKK, youth organizations and the community.